“Vastness and Profundity”: Sublimity and Religion in Post-1960 Science Fiction - Garton-Gundling, Kyle (Religion and the arts, 2024)
Scholars have often struggled to define the boundaries between sublime and religious experiences, but research tends to agree that sublimity is rational while religious experience is non-rational. However, this view receives a challenge from key texts in science fiction. In the texts I examine, contrary to prevailing views, sublimity turns mystical, while new religions become rational. Furthermore, religion and sublimity relate uneasily, as opposite poles that are distinct from but necessary to one another, with different texts emphasizing one while marginalizing, but not erasing, the other. I explore four authors, two of whom—Arthur C. Clarke and Liu Cixin—emphasize sublimity while relegating religion, while the other two—Robert A. Heinlein and Octavia E. Butler—focus on a fictional religion while subordinating the sublime. Taken together, these texts reveal the ambivalent interdependence of rational and non-rational states of mind in ways that could promote better understanding between religious and non-religious perspectives.